EFFECT OF OVSYNCH ON PREGNANCY RATE IN CROSSBRED HEIFERS - Vijayarajan, A; Chandrahasan, C; Napolean, R Ezakial (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Synchronization of ovulation (Ovsynch) was tested in 10 crossbred heifers using Gonadotropin Releasing Hormone (GnRH) and Prostaglandin F2α (PGF2α). Another 10 heifers served as control and were inseminated at detected estrous. The onset of estrus was synchronized in Ovsynch group and the percentage of induced estrus was 100 per cent. The first service conception rate was lower for Ovsynch group than the control group. But three animals conceived in the Ovsynch group and none conceived in the control group of animals during the second service.
Keywords: Heifers; Synchronization; Timed insemination; GnRH